Implementasi Model Budidaya Udang Galah Berbasis Eco-Masjid di Kendari - Akhmad Mansyur; Roslindah Daeng Siang; Muhaimin Hamzah; La Ode Muhamad Aswan (Civiliza Publishing, 2026)
The development of mosques as centres for sustainable community empowerment is an important issue in the socio-economic development of urban communities. This activity aims to implement and analyse a model for giant prawn (Macrobrachium rosenbergii) farming based on eco-mosques in the Tawang Alun 2 Complex, Kendari City. The approach used is the application of science and technology with a Participatory Action Research (PAR) approach. As a result, it was revealed that the integration of eco-mosque principles with giant river prawn farming allows for the optimisation of limited land, efficient water use, environmentally friendly waste management, and the strengthening of the congregation's economy. The developed model encompasses technical aspects of farming, mosque institutional aspects, congregation participation, and environmental sustainability. This programme has the potential to increase community income, support local food security, and strengthen the role of mosques as centres of worship, education, and community economy. This model is recommended as an alternative for developing productive eco-mosques that can be replicated in other urban areas